Oesophageal intramural pseudodiverticulosis presenting as non‐resolving pneumonia: A sinister cause diagnosed by EUS‐B‐FNA. Issue 12 (24th November 2021) - Joshi, Sharad; Majumdar, Subhasish; Bhatia, Ankit; Tayal, Nitesh
Abstract: We report a case of an oesophageal intramural pseudodiverticulosis leading to a mediastinal collection caused by Candida glabrata presenting as a non‐resolving pneumonia and mimicking an oesophageal mass. The patient was a 60‐year‐old diabetic male who was referred from another hospital and presented with a history of low‐grade fever and breathlessness. His computed tomography (CT) of the chest disclosed a mediastinal mass alongside the oesophagus with pleural collection. Endobronchial ultrasound scope was inserted through the oesophagus (EUS‐B) and fine‐needle aspirate was taken from the mass. The cultures of specimen from the mediastinum grew drug‐resistant C . glabrata . The patient was managed with oral voriconazole along with oesophageal stenting after which he showed remarkable recovery. Repeat CT revealed a near‐complete reduction of the mediastinal infection. The case highlights the need of a high degree of suspicion, right approach to diagnostic work‐up and appropriate histopathological and microbiological examination of clinical specimens. Abstract : We report a case of an oesophageal intramural pseudodiverticulosis leading to a mediastinal collection caused by Candida glabrata presenting as a non‐resolving pneumonia and mimicking an oesophageal mass. The case highlights the need of a high degree of suspicion, right approach to diagnostic work‐up and appropriate histopathological and microbiological examination of clinical specimens.